Analisis Dampak Implementasi Dana Desa dan Alokasi Dana Desa terhadap Tata Kelola Pemerintahan, Kualitas Layanan Publik, Dan Kesejahteraan Masyarakat Desa (Studi Pada Desa di Kecamatan Batang Cenaku, Kabupaten Indragiri Hulu, Provinsi Riau) - Suwaji Suwaji; Suharmiyati Suharmiyati (J-MAS (Jurnal Manajemen dan Sains), 2020)
The government policy of disbursing Village Funds and Village Fund Allocation is a breakthrough that is able to provide new enthusiasm for the implementation of rural development, where village funds obtain a clear source, direction of implementation, supervision and reporting system, it is expected to be able to spur improvement in village governance and grow impact on improving the welfare of the village or village community. The research was carried out in the village in the scope of Batang Cenaku District, Indragiri Hulu Regency, Riau Province. The research objective is to get an idea of the extent of the impact of the implementation of village funds on village governance, the quality of public services, and the welfare of village communities. This study uses primary and secondary data with a quantitative descriptive approach, from questionnaires that have been successfully distributed and collected then conducted a descriptive analysis, to test hypotheses using SPSS program tools. The results of the analysis that have been done show that the implementation of village funds has a positive impact on governance, implementation of village funds and allocation of village funds have a positive impact on the quality of public services, and implementation of village funds and allocation of village funds have a positive impact on the welfare of the community in the village, however if viewed more closely, the impact of implementing village funds and allocation of village funds on village governance is higher than the impact of implementing village funds on the quality of public services, and the impact of implementing village funds and allocation of village funds in improving the welfare of village communities.